Reducing wait times for access to inpatient rehabilitation for patients with acquired brain injury: a quality improvement initiative - Rebecca Fleck; Ramona Neferu (BMJ Open Quality)
Background Acquired brain injury (ABI) is a major cause of disability. Timely access to inpatient ABI rehabilitation is associated with improved outcomes at the patient, system, and societal levels.Problem Wait times to access the inpatient ABI rehabilitation programme at the local regional rehabilitation centre by patients referred from community hospitals were consistently greater than provincial targets and benchmarks.Objective This initiative aimed to reduce the mean wait times from referral to admission by 30% (from 27 to 19 days) during the 12-month project period. The secondary aim was to concurrently achieve a reduction in the mean wait times for decisions from 9.5 to 5 days during the same period.Methods A non-randomised time-series design was undertaken. Baseline and postintervention wait times were obtained from patient intake charts. Process mapping, value analysis and five-why analysis were used to identify root causes for delays in the intake process. Referring hospital staff and the ABI Rehab interdisciplinary team members were engaged in change idea development and refinement. Iterative Plan-Do-Study-Act cycles were used to improve the change ideas’ usability and uptake. Data analysis was performed using the QI Macros package in Microsoft Excel.Results Root causes for delays included frequent incomplete referrals, variability in the intake process and limitations in rehab bed availability. Two change ideas were introduced: (1) a standardised intake protocol and (2) a referral checklist. Within 3 months, the mean decision wait times were reduced to 4 days (58% reduction), and the mean admission wait times were reduced to 12 days (54% reduction).Conclusion This initiative led to the systematic standardisation of the intake process for the local regional ABI rehab programme. Wait time improvements surpassing the initial aims were observed and may inform future benchmarks.